Outbreak Investigation: Jamestown Canyon Virus Surveillance in Field-Collected Mosquitoes (Diptera: Culicidae) From Wisconsin, USA, 2018–2019 - Farquhar, Melissa R.; Thrun, Nicholas B.; Tucker, Bradley J.; Bartholomay, Lyric C. (Frontiers in Public Health, 2022)
During the summers of 2017–2019, 60 human cases of Jamestown Canyon virus-associated disease were reported in the State of Wisconsin, U.S.A; by comparison, there were 28 cases in the 5 years prior. Jamestown Canyon virus (JCV, Peribunyaviridae: Orthobunyavirus) is a zoonotic, mosquito-borne virus that is endemic throughout North America. The proposed transmission cycle for JCV involves horizontal transmission by a variety of mammal-feeding mosquito species and deer hosts, and transseasonal maintenance by vertical transmission in Aedes mosquito species. Although some of the earliest work on JCV transmission and disease was done in Wisconsin (WI), little is known about the spectrum of mosquitoes that are currently involved in transmission and maintenance of JCV, which is key to inform the approach to control and prevent JCV transmission, and to understand why case numbers have increased dramatically in recent years. Therefore, we undertook an intensive surveillance effort in Sawyer and Washburn counties, WI between April and August of 2018 and 2019, in an area with a concentration of JCV human cases. Larval and adult stages of mosquitoes were surveyed using larval dippers and emergence traps, light traps, resting boxes, a Shannon-style trap, and backpack aspirator. In total, 14,949 mosquitoes were collected in 2018, and 28,056 in 2019; these specimens represent 26 species in 7 genera. Suspect vector species were tested for JCV by polymerase chain reaction (PCR); of 23 species that were tested, only Aedes provocans yielded JCV positive results. In 2018, a single pool of Ae. provocans tested positive. In 2019, with more focused early season surveillance, we detected JCV in 4 pools of adult mosquitoes, and one pool that consisted of lab-raised adults that were collected as larvae. Material from all of these PCR-positive samples also yielded infectious virus in cell culture. Overall, these data provide new insight into the seasonality and habitat preferences for 26 mosquito species in Northern WI, which will be useful to inform future surveillance efforts for JCV. The results underscore the importance of Ae. provocans as a vector species involved in transseasonal maintenance of JCV in this region.